Hold the device against the skin: the impact of injection duration on user's force for handheld autoinjectors. (1st February 2020) - Schneider, Andreas; Mueller, Philippe; Jordi, Christoph; Richard, Philipp; Sneeringer, Peter; Nayyar, Ranjan; Yovanoff, Mary; Lange, Jakob
ABSTRACT: Background : The recent development of high-volume subcutaneous drug delivery using handheld autoinjectors has resulted in longer injection durations. However, the usability of long injections has been neglected. This study aimed to investigate the effects of injection duration on users' ability to apply injections while holding the device against the skin at the injection site. Methods : Thirty-two participants among patients, caregivers, and health-care professionals simulated three injections with different injection durations to evaluate usability and user's force. Linear and quantile regression were then applied to determine the impact of the injection duration on response variables related to user's force. Results : A significant negative effect of injection time was found on both the minimum and mean user's force applied. Initial empirical evidence was also determined on the negative association being more pronounced for users exerting lower force to hold the device against the skin. Conclusions : The results that are subject to future clinical validation suggest the feasibility of injections lasting up to approximately 30 s using handheld autoinjectors. The participants of the simulated use study successfully applied long-duration injections regardless of disease states, age, or visual and dexterity impairments.